Effect of inflammatory bowel disease and related medications on COVID-19 incidence, disease severity, and outcome: the Israeli experience. Issue 3 (March 2022) - Richter, Vered; Bermont, Anton; Cohen, Daniel L; Broide, Efrat; Shirin, Haim
Abstract : Objectives: The coronavirus disease 2019 (COVID-19) pandemic raised concerns among inflammatory bowel disease (IBD) patients fearing an increased risk of infection and poor outcomes. We aimed to evaluate the incidence of COVID-19 among IBD patients; its influence on disease severity and outcome; its relationship to medication use and how the pandemic affected IBD management. Methods: An anonymous questionnaire was posted online to members of the Israel Crohn's Disease and Ulcerative Colitis Foundation (November 2020–January 2021). The questionnaire addressed the course of IBD disease and COVID-19 infection over the past year. Results: Total 2152 IBD patients completed the questionnaire. Of which 104 (4.8%) had been infected with COVID-19, significantly lower than the 'expected' infected cases among the Israeli population ( P  = 0.033). The median age of participants was 39 years; 60.5% were female. Most patients (75.6%) had no comorbidities other than IBD. No correlation was found between IBD type or disease severity and COVID-19 infection. Most IBD patients reported mild COVID-19 disease, regardless of the type of IBD medications. Multivariable logistic regression analysis revealed that younger age, elevated BMI and diabetes were independent risk factors for COVID-19 infection. IBD treatment methods including 5-aminosalicylic acid, smoking and hypertension were protective factors. In total 25.2% of COVID-19 patients discontinued their IBD treatment, compared to 8.5% of non-COVID-19-infected patients. IBD flares were significantly higher in those who discontinued treatment ( P  < 0.001). Conclusions: IBD patients do not have an increased risk for COVID-19, regardless of IBD activity or treatment. Patients should be encouraged to continue effective IBD therapy, including biologics and steroids, to minimize active IBD. Abstract : Supplemental Digital Content is available in the text.